Інтертекстуальність і переклад - Мельник, Л. (Філологічний дискурс, 2017)
У статті подано стислий огляд підходів до визначення поняття
«інтертекстуальність». Узагальнено основні підходи до розуміння
терміну «інтертекстуальності». Виявлено й обґрунтовано
оптимальні перекладацькі рішення, які зумовлені специфікою
художніх текстів. Встановлена специфіка взаємодії
інтертекстуальності та перекладу. З урахуванням цього
сформульовано принципи перекладу інтертекстуальних одиниць у художньому творі. This article represents a brief theoretical overview on the definition of
«intertextuality». The paper deals with the terms intertext and intertextuality.
Special attention has been paid to the formation of intertextual ties of «text in text»
and «text within texts» types. The approaches to the definition of the category of
intertextuality are suggested. Intertextuality is defined as interspersing a text with
other texts in the form of quotations, allusions and reminiscences. The original
essence of the term «intertextuality», introduced into linguistic usage by
poststructuralist Julia Kristeva as the synthesis of structural semiotics and
plurality of meanings in every belles-lettres text, is considered. An emphasis is laid
on the elucidation of the conventionally used in linguistics terms, for the nomination
of which the term «intertextuality» is applied for the modish purpose. The relevance
of the given research is caused by the general tendency of combined researches in
linguistics that foresee analysis of the whole body of external and internal
connections of a text of fiction and means of their realization in the explicitly
intertextual process of functioning of the text. The aim of the paper is an attempt to
define basic regulation for the linguistic theory of intertextuality, which preconditions scientific novelty the paper.